Pelatihan pembuatan nugget pisang sebagai upaya pemberdayaan masyarakat berbasis komoditas lokal di Kabupaten Majene: Banana nugget production training as an effort to empower the community based on local commodities in Majene Regency - Achmad Nur Syawal Alwi; Nurul Wakiah; Trinoviyani; Indrastuti; Sudirman (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
Community service activities carried out in the form of banana nugget-making training are part of an effort to improve community knowledge and skills in processing local commodities. This activity was carried out in Bonde Village, Pamboang District, Majene Regency, West Sulawesi Province, on December 17, 2024. The stages of the activity include preparation, presentation of training materials, training practice, and monitoring and evaluation. Twenty participants, aged 23-60 years, who were housewives and MSME business actors, attended this training. Developing knowledge about banana processing, a better understanding of banana nugget processing, knowing the benefits of banana processing diversification, and getting more people interested in making and selling banana nugget products are all signs that the activities were successful. Based on monitoring and evaluation data, this activity succeeded in increasing participant knowledge and understanding regarding the benefits and process of converting bananas into banana nuggets. This training also increased participants' interest in making and selling banana nugget products.